Selling the price increase the ultimate B2B field guide for raising prices without losing customers - Blount, Jeb (Wiley, 2022)
"Price increases play an integral role in the profitability of businesses. They protect the enterprise during inflationary periods, produce capital for investment in growth, protect jobs, help improve quality and service delivery, and boost stock prices. Price increases are the fastest and most effective way for companies to drive both top line and bottom-line improvements. That is, of course, if you retain your customers along the way. Customer retention is exactly why B2B companies lean so heavily on their sales teams to execute price increase campaigns. Sales professionals have the most intimate knowledge of the customer base, are skilled communicators, and professional closers. It should be the perfect combination to make price increases stick without losing customers. Except that sales professionals express deep anxiety over price increase initiatives. They fear that they will lose customers and permanently damage important relationships. In overwhelming numbers, they say that they lack the skills and confidence to approach price increase conversations effectively. Compounding this deficiency in confidence is the fact that most companies provide little to no formal training for selling price increases or for frontline leaders who must coach this critical skill set. Since more than 80% of training dollars are invested in training business development and top of funnel sales skills, most sales professionals and leaders are not going to receive professional training for selling price increases. At the same time, in our current economic climate and inflationary period, executives are exerting massive pressure on their sales organizations to engage customers and get price increases. Selling the Price Increase is as an easily executable tactical field guide for both frontline sales professionals and sales leaders who want to gain the confidence to be successful with price increase conversations"--
Includes index. - Description based on print version record and CIP data provided by publisher; resource not viewed
Keywords: Willingness to pay; Selling; Business communication; Consentement à payer; Vente; Communication dans l'entreprise; selling